Analisis manajemen risiko pada Coze Coffee Shop: Strategi mitigasi untuk keberlanjutan bisnis - Pangestuti, Dewi; Sumilir, Sumilir; Munasiron, Munasiron; Nastiti, Heni (PT WIM Solusi Prima, 2025)
The objective of this community service initiative is to conduct a comprehensive analysis of the risk management strategies employed by Coze Coffee Shop, a micro, small, and medium enterprise (MSME) operating within the coffee shop sector in Indonesia. The primary objective of this study is to identify, evaluate, and formulate risk mitigation strategies that can enhance business sustainability. The approach employed is qualitative descriptive, with data collection techniques including interviews and direct observation. The findings of the study suggest that Coze Coffee Shop is confronted with a multitude of operational, market, financial, and human resource risks. Mitigation measures that have been implemented include product innovation, service improvement, the use of social media for marketing, and more efficient cash flow management. The results of this community service provide recommendations for improving risk management that is more adaptive and responsive to dynamic market changes, as well as the importance of strengthening human resource capacity to address the challenges of the increasingly competitive coffee shop industry. It is hypothesized that the results of this community service will contribute to the development of effective risk management strategies for MSMEs in the coffee shop sector and have a positive impact on their business sustainability amid intense competition. Pengabdian pada masyarakat (PKM) ini bertujuan untuk menganalisis manajemen risiko yang dihadapi oleh Coze Coffee Shop, sebuah usaha mikro, kecil, dan menengah (UMKM) di sektor kedai kopi di Indonesia. Fokus utama penelitian ini adalah untuk mengidentifikasi, mengevaluasi, dan merumuskan strategi mitigasi risiko yang dapat meningkatkan keberlanjutan bisnis. Pendekatan yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara dan observasi langsung. Hasil penelitian menunjukkan bahwa Coze Coffee Shop menghadapi berbagai risiko operasional, pasar, keuangan, dan sumber daya manusia. Beberapa langkah mitigasi yang telah diterapkan meliputi inovasi produk, perbaikan layanan, penggunaan media sosial untuk pemasaran, serta pengelolaan arus kas yang lebih efisien. Hasil PKM ini memberikan rekomendasi untuk meningkatkan pengelolaan risiko yang lebih adaptif dan responsif terhadap perubahan pasar yang dinamis, serta pentingnya penguatan kapasitas sumber daya manusia untuk menghadapi tantangan industri kedai kopi yang semakin kompetitif. Hasil PKM ini diharapkan dapat memberikan kontribusi dalam pengembangan strategi manajemen risiko yang efektif bagi UMKM di sektor kedai kopi, serta memberikan dampak positif terhadap keberlanjutan bisnis mereka di tengah persaingan yang ketat.